Porphyromonas gingivalis Suppresses Differentiation and Increases Apoptosis of Osteoblasts From New Zealand Obese Mice. Issue 9 (1st September 2015) - Dittmann, Cora; Doueiri, Salim; Kluge, Reinhart; Dommisch, Henrik; Gaber, Timo; Pischon, Nicole
Abstract : Background: Metabolic syndrome (MetS), a complex cluster of risk factors for chronic diseases such as cardiovascular disease, is observed to be increasingly associated with periodontal disease. However, the fundamental contribution of periodontal bacteria to periodontal bone loss in patients with MetS remains unclear. The aim of the present study is to analyze the effect of Porphyromonas gingivalis on differentiation of primary osteoblasts from New Zealand obese (NZO) mice, a model for MetS, compared with C57 Black 6 JAX (C57BL/6J) mice osteoblasts. Methods: Primary calvarial osteoblasts, isolated from 3‐day‐old NZO and control C57BL/6J mice, were stimulated with P. gingivalis . Proliferation was quantified by 5‐bromo‐2′‐deoxyuridine incorporation. Cell cycle and early and late apoptosis were measured by flow cytometry. Gene expression was determined by real‐time polymerase chain reaction (RT‐PCR). Results: Twelve hours after P. gingivalis stimulation, NZO osteoblasts showed significantly decreased proliferation ( P ≤0.01) with increased G2 cell cycle phase compared with normal osteoblasts. Flow cytometry analysis demonstrated significant ( P ≤0.01) increase of early apoptotic cells (annexin V positive) and late apoptosis (caspase 3 activity) in NZO cells compared with control cells at 3 and 6 hours after stimulation. No significant lactate dehydrogenase release was found after P. gingivalis stimulation. RT‐PCR data showed significantly suppressed expression ( P ≤0.01) of collagen 1, osteocalcin, and Runt‐related transcription factor 2 in NZO cells compared with normal osteoblasts. Conclusions: The present data demonstrate that P. gingivalis downregulates proliferation and promotes apoptosis in primary NZO osteoblasts, unlike C57BL/6J osteoblasts. Also, suppressed osteoblastic marker expression in NZO cells may contribute to pathogenesis of periodontitis, suggesting a similar process in patients with MetS.